Effect of Parenting Style on the Incidence of Sibling Rivalry in Children in Surakarta, Central Java - Ropitasari; Nindy Widiastuti; Fanny Kartika Fajriyani; Nahdiyah Karimah (Journal of Epidemiology and Public Health, 2025)
Background: Proper parenting can reduce incidents of jealousy, competition, or arguments. (siblings' rivalry) a child towards the presence of a new sibling. One solution to the sibling effect rivalry through parents who encourage children to change their behavior, knowledge, and values that are considered appropriate so that children can be independent, grow and develop healthily and optimally, and have a sense of believe self, characteristic flavor want to know, friendly, and oriented towards progress without drop the one others. This study aimed to analyze the influence of parenting patterns on sibling rivalry in children in Surakarta.Subjects and Method: This study employed a cross-sectional design and was conducted in the Sangkrah area, Surakarta, Indonesia. The study population consisted of parents who had more than one child under the age of five. A total of 120 respondents were selected using systematic random sampling. The independent variable in this study was parenting patterns, while the dependent variable was sibling rivalry, which was measured using a nominal scale. Data were collected directly through a structured questionnaire. The data were then analyzed using bivariate analysis with the Chi-Square test.Results: The study showed that 77.5% (93 children) experienced sibling abuse. rivalry among them, 7 people have an authoritarian parenting style (5.8%), 101 people have a democratic (84.2%), 78 people have a permissive (65%), and 11 parents have a passive (9.2%). Permissive (OR= 1.65; 95% CI= 0.68 to 3.98) and passive parenting style (OR = 2.29; 95% CI = 0.54 to 9.66) increased the likelihood of sibling rivalry, by the associations were statistically non-significant.Conclusion: There is no significant influence of the four parenting patterns on sibling incidents. rivalry is insignificant.